Case Report: Fluoroless implantation of left branch bundle pacing in a pregnant patient - Li, Jun; Li, Xiaofang; Zhang, Anxin; Li, Fanqi; Wang, Haixiong (Frontiers in Cardiovascular Medicine, 2023)
A pregnant patient had symptomatic atrial standstill and indications for pacing therapy with an expected high ventricular pacing ratio. With the consideration of potential pacing-induced cardiomyopathy in the future we conducted zero-fluoro left bundle branch pacing (zLBBP) implantation for heart failure prevention. An ex vivo 3D cardiac model (Medtronic, USA) was used preoperatively to simulate the zLBBP implantation to improve procedure safety and efficiency. Intraoperatively, the simulation steps were followed, and a combination of electroanatomic navigation systems (EANS) and intracardiac echocariography (ICE) were used to ensure that the procedure was performed efficiently and safely.